2022
DOI: 10.1021/jacs.2c00743
|View full text |Cite
|
Sign up to set email alerts
|

Compact Peptoid Molecular Brushes for Nanoparticle Stabilization

Abstract: Controlling the interfaces and interactions of colloidal nanoparticles (NPs) via tethered molecular moieties is crucial for NP applications in engineered nanomaterials, optics, catalysis, and nanomedicine. Despite a broad range of molecular types explored, there is a need for a flexible approach to rationally vary the chemistry and structure of these interfacial molecules for controlling NP stability in diverse environments, while maintaining a small size of the NP molecular shell. Here, we demonstrate that lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 119 publications
0
15
0
Order By: Relevance
“…Designing peptoids for various biomaterials applications requires synthetic versatility, which has remained a challenge in solution-phase peptoid synthesis. Increasing the variety of accessible side chains provides opportunities to explore the influence of functional groups on different application-relevant properties such as self-assembly, biological activity, and biorecognition. Most solution-phase peptoid research has focused on linear alkyl side chains because the polymerization rate has been shown to be affected by side chain length and bulkiness. Density functional theory (DFT) calculations have shown that steric hindrance of beta-branched alkyl side chains contributes to reduced rates of polymerization and van der Waals interactions lead to aggregation for linear and gamma-branched side chains .…”
Section: Optimizing the Solution-phase Synthesis Of Peptoidsmentioning
confidence: 99%
“…Designing peptoids for various biomaterials applications requires synthetic versatility, which has remained a challenge in solution-phase peptoid synthesis. Increasing the variety of accessible side chains provides opportunities to explore the influence of functional groups on different application-relevant properties such as self-assembly, biological activity, and biorecognition. Most solution-phase peptoid research has focused on linear alkyl side chains because the polymerization rate has been shown to be affected by side chain length and bulkiness. Density functional theory (DFT) calculations have shown that steric hindrance of beta-branched alkyl side chains contributes to reduced rates of polymerization and van der Waals interactions lead to aggregation for linear and gamma-branched side chains .…”
Section: Optimizing the Solution-phase Synthesis Of Peptoidsmentioning
confidence: 99%
“…In the presence of an external potential, the free energy of the system brush is expressed as (5) where P and C are the self-consistent parameters determined by the physical constraints of the grafted polymer chain and counterions, respectively.…”
Section: Polymer Density Functional Theorymentioning
confidence: 99%
“…Polymer brushes (PBs) are assembled by anchoring polymeric chains onto a surface, triggering an increasing interest due to the unique chemical and structural characteristics of polymeric chains. 1-2 So far, PBs have made significant contributions to a broad range of traditional and emerging applications such as biological lubrication 3 , thermal and electrical stimuli-responsive surface 4 , colloidal stabilization and surface protection 5 , novel substrate modification, 6-7 biosensing and nanomaterial synthesis, etc. 8 These applications are highly dependent on the interfacial microstructure of PBs and straightforwardly benefited from its precise tuning.…”
Section: Introductionmentioning
confidence: 99%
“…Significant efforts have been dedicated to surface functionalization of NPs in order to prevent their aggregation, which can be achieved through two main approaches: (1) chemical modification, which includes both “graft to” and “graft from” methods, and (2) physical adsorption of dispersants. These studies have provided both theoretical and experimental foundations for modifying effectively surface structure of NPs to prepare stable dispersion systems. In the case of pigments, introducing reactive groups on the surface and utilizing sequence condensation reactive has led to stronger stability of pigment suspensions .…”
Section: Introductionmentioning
confidence: 99%